Culture and commitment: a study of the generation gap - Mead, Margaret (New York: Doubleday, 1970)
Margaret Mead explains how the youth of her generation differs from those in the past and why an unprecedented generation gap must be acknowledged by old and young alike before communication can begin. Condition: Previous owner's name on pastedown. Jacket slightly soiled, spine heal has 3/4" chip, tear at front corner and heal of spine else a very good copy in like jacket.
Keywords: ANTROPOLOGY; CIVILIZATION; SOCIAL CONFLICTS; YOUTH